Good teacher education – an exploratory study - Venter, Elza (The IIE, 2017)
Good or effective education of prospective teachers in traditional higher education settings seemingly differ from educating them in Open Distance Learning (ODL). The literature was reviewed with reference to ‘good teacher education’ in traditional higher education and that in ODL contexts. Content analysis was done with the responses to two open-ended questions, e-mailed to staff members of the Department of Teacher Education in the College of Education at an ODL institution, namely ‘What is good teacher education?’ and ‘What is good teacher education in ODL?’ Since the researcher is part of the College of Education, she made use of convenience sampling. In comparing literature with the empirical findings it seems that good teacher education contains many of the same elements in ODL and traditional higher education settings. The context in ODL teacher education is different, but all student teachers need particular generic skills and competences. Interactive digital communication technologies are, however, more extensively used in ODL. Recommendations on how teacher education in both settings can be improved are made.
Keywords: Teacher education; Higher education; Distance education; Teaching skills; Digital technologies; Social media